Modifying, standardizing and adapting the Adverse Childhood Experience Questionnaire (Ukrainian Journal of Ophthalmology, 2025)
Background: Medical and social workers and psychologists are increasingly faced with challenges relating to the management of the impact of adverse childhood experiences (ACE) on patient’s health and feeling of mental wellbeing. Consequently, it is important to develop psychodiagnostic instruments for detecting ACE and to adapt them to the social and cultural realities of the Ukrainian environment.Purpose: To modify, standardize and adapt the Ukrainian version of the ACE Questionnaire.Material and Methods: A sample of 230 respondents aged 18 to 70 years was included in this study. A modified version of the original ACE Questionnaire by Felitti, Anda and colleagues was used in the study.Results: The original items were translated and modified, and the resultant questionnaire was validated. Cronbach's Alpha test was conducted to test internal reliability, and factor analysis, (a) to determine the number and structure of factors describing the covariance structure of the data and (b) to confirm the construct validity of the instrument. In addition, the instrument was standardized by calculating percentile ranks, Z-score normalizing and reporting the scores as stanines. As a result, an advanced Ukrainian version of the instrument was obtained, comprising three main subscales and the additional subscale with 22 items totally. Therefore, the adapted Ukrainian version of the ACE Questionnaire is characterized by high construct validity and reliability.
Keywords: ACE; adverse childhood experience; questionnaire; standardization; modification; reliability; validity